Existence of solutions for a sequential fractional integro-differential system with coupled integral boundary conditions. (November 2017) - Ahmad, Bashir; Luca, Rodica
Abstract: We investigate the existence and uniqueness of solutions for a system of nonlinear Caputo type sequential fractional integro-differential equations with coupled Riemann–Stieltjes integral boundary conditions, by using the Leray–Schauder alternative and the Banach contraction principle. Two examples are also presented to illustrate our results.